Digitalisasi Pendidikan Islam di Perguruan Tinggi Islam: Kebijakan Riset Berbasis Data untuk Membangun Generasi Moderat - Yusuf Hidayat; Ahmad Arifi (J-MPI (Jurnal Manajemen Pendidikan Islam), 2025)
The digitalization policy of Islamic education in the Master of Islamic Education (PAI) Program with a concentration in Islamic Religious Education Management and Policy (MKPAI) at the State Islamic University (UIN) Sunan Kalijaga Yogyakarta, using a qualitative case study approach that combines in-depth interviews, document analysis, and observation of the implementation of e-learning platforms and digital literacy training. The results show that digitalization through e-learning platforms and data analytics has increased the flexibility and personalization of learning, while effectively internalizing the value of religious moderation through online discussion forums, problem-solving simulations, and digital reflection assignments, thus supporting the formation of a moderate generation that is tolerant, inclusive, and competitive in the digital era. However, implementation still faces various challenges such as technological infrastructure gaps (especially internet access in rural areas), academic cultural resistance to digital change, low digital competency of lecturers (only around 45% have digital literacy certification), and suboptimal student engagement in the platform's interactive features. The main opportunity lies in the development of data-driven research policies to optimize educational governance, personalize learning, and collaborate across institutions in accordance with the vision of Merdeka Belajar. Recommendations include strengthening technological infrastructure, intensive digital literacy training for lecturers and students, and adopting a hybrid learning model to create a more inclusive, moderate, and adaptive Islamic education to the dynamics of the digital era.